2021
DOI: 10.1080/1331677x.2021.1936112
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 shocks on the volatility of stock markets in technologically advanced countries

Abstract: This study examines the volatility of China and the most advanced countries of the world stock markets due to the pandemic of COVID-19 using the TGARCH model. This research study presents empirical support for the TGARCH specification for explaining the daily time dependence in the rate of information arrival to the market for stocks traded on China stock market. Using the sample containing closing stock market returns from 05 January 2015 to 04 April 2020 of sample countries, we found that through the COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 67 publications
1
18
0
1
Order By: Relevance
“…Compared to modern history pandemics, COVID-19 comes at a larger scale ( Khatatbeh, Hani, & Abu-Alfoul, 2020 ). Zhang, Wang, and Nosheen (2021) consider COVID-19 as one of the biggest pandemics in history. The real economy is severely hit by COVID-19 ( Albulescu, 2021 ).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Compared to modern history pandemics, COVID-19 comes at a larger scale ( Khatatbeh, Hani, & Abu-Alfoul, 2020 ). Zhang, Wang, and Nosheen (2021) consider COVID-19 as one of the biggest pandemics in history. The real economy is severely hit by COVID-19 ( Albulescu, 2021 ).…”
Section: Related Literaturementioning
confidence: 99%
“…Nevertheless, the market is going to correct itself as more information becomes more available with time ( Phan & Narayan, 2020 ; Yan et al, 2020 ). Zhang et al (2021) argue that the stock market could be badly affected by COVID-19 in the long run. So, it is too early to be certain of the pandemic effects ( Khatatbeh et al, 2020 ).…”
Section: Related Literaturementioning
confidence: 99%
“…A hallmark of the current crisis is the extraordinary volatility of the financial markets. 21 The analysis of responses revealed that at the individual socio‐ecological level many participants felt financially worse off because of COVID‐19. This was attributed to the consequential decline in interest rates, the increased volatility in financial markets and the loss of rental income.…”
Section: Resultsmentioning
confidence: 99%
“…Now the novel coronavirus also caused great oscillations across the world. Some researchers found substantial evidence of significant impact of coronavirus on developed markets (Ali et al, 2020;Zhang et al, 2021b;Song et al, 2021;Youssef et al, 2021;Gao et al, 2021). But studies aimed at investigating the impact of covid-19 on the international linkages of Indian stock market with other countries are in dearth.…”
Section: Statement Of Problemmentioning
confidence: 99%